2010
DOI: 10.1007/s00167-010-1201-6
|View full text |Cite
|
Sign up to set email alerts
|

Causes for failure of ACL reconstruction and influence of meniscectomies after revision

Abstract: The purpose of this multicenter retrospective study was to analyze the causes for failure of ACL reconstruction and the influence of meniscectomies after revision. This study was conducted over a 12-year period, from 1994 to 2005 with ten French orthopaedic centers participating. Assessment included the objective International Knee Documenting Committee (IKDC) 2000 scoring system evaluation. Two hundred and ninety-three patients were available for statistics. Untreated laxity, femoral and tibial tunnel malposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(166 citation statements)
references
References 41 publications
6
152
1
4
Order By: Relevance
“…In the present study, tunnel positioning in the primary ACL reconstruction was correct in only 6 out of 34 patients (17.6%). Malposition of the femoral tunnel accounted for primary graft failure in 28 cases (82.4%), which was at the high end of the previously reported range (37-85%) (28)(29)(30)(31). The lesions of the anterior cruciate ligament identified intra-operatively in the present study included graft absorption (n=4, 11.8%), ACL rupture (n=10, 29.4%) and ACL laxity (n=20, 58.8%).…”
Section: Discussionsupporting
confidence: 44%
“…In the present study, tunnel positioning in the primary ACL reconstruction was correct in only 6 out of 34 patients (17.6%). Malposition of the femoral tunnel accounted for primary graft failure in 28 cases (82.4%), which was at the high end of the previously reported range (37-85%) (28)(29)(30)(31). The lesions of the anterior cruciate ligament identified intra-operatively in the present study included graft absorption (n=4, 11.8%), ACL rupture (n=10, 29.4%) and ACL laxity (n=20, 58.8%).…”
Section: Discussionsupporting
confidence: 44%
“…Parkinson et al [31] found that meniscal integrity was the strongest predictor of ACL reconstruction failure. Increased graft laxity was found in ACL reconstruction patients with medial meniscal deficiency [32], and a higher incidence of a residual pivot shift was reported in meniscal-deficient knees [33]. Greater stress through the ACL graft in meniscal-deficient knees may explain a higher graft failure rate [31].…”
Section: Late Post-operative Complicationsmentioning
confidence: 98%
“…For a variety of reasons a considerable number of patients are not satisfied or experience pain after anterior cruciate ligament (ACL) reconstruction [1][2][3][4][5]. Typical reasons include failure of the ACL graft, failure of graft fixation, chronic synovitis due to biodegradable fixation material and missed concomitant injuries [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Typical reasons include failure of the ACL graft, failure of graft fixation, chronic synovitis due to biodegradable fixation material and missed concomitant injuries [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%